Micro-ancoragens - Craizer, Waldemar (1981)
This thesis presents and discusses a new constructive system called ''micro-anchorage'', which has been used, associated to walls, to retain fills. This system is basically constituted by plates, horizontally placed inside the fill, connected by ties to the retaining wall or to another structure. Those retaining structures can be sheet walls, as in case of the herein described applications, the plates can be small reinforced concrete slabs and the ties can be steêl wires 8mm diameter used in prestressed concrete. Each micro-anchorage is prestressed and teste d as a grouted anchorage, from which eh it differs, among other aspects, by its reduced working load(about 3. Otf). The first five jobs in which this method was used are described. The design procedures used in these jobs followed those for conventional anchored walls in use for more than twenty years; these procedures are described here together with a solution, believed original, for determining the free length of the anchorage. Besides the routine "acceptance" tests (with satisfactory results), in two of the mentioned jobs, supplementary micro-anchorage were introduced, in limited quantity, for more controlled tests. The basic intention was to induce failure before the maximum test load of 6,0/6,5 tf, approximately the limit load of the 8mm diameter wire (CP 150 RN), used as tie. For that purpose, the supplementary anchor slabs were significantly shorter and were placed at shallower depths. ln fact, only a small number of failures occurred, confirming the safety of the jobs. The test. results were discussed and allowed recommendations for a more economic design of micro-anchorages. An interpretation of test results based on analytical expressions, developped after hypothesis of the failure mecanism, was tried. Considering the small number of failures which occurred, within the also small number of test anchors, little can be said about the reliability of those expressions. New tests, in a larger number and with ties of higher capacity (which can take the anchors to failure) are indicated; model tests, for determining the failure mechanism, are also recommended.